Hierarchic micro-patterned porous scaffolds via electrochemical replica-deposition enhance neo-vascularization. (21st April 2016) - Varoni, Elena Maria; Altomare, Lina; Cochis, Andrea; GhalayaniEsfahani, Arash; Cigada, Alberto; Rimondini, Lia; De Nardo, Luigi
Abstract: Neo-vascularization is a key factor in tissue regeneration within porous scaffolds. Here, we tested the hypothesis that micro-patterned scaffolds, with precisely-designed, open micro-channels, might help endothelial cells to produce intra-scaffold vascular networks. Three series of micro-patterned scaffolds were produced via electrochemical replica-deposition of chitosan and cross-linking. All had regularly-oriented micro-channels ( ϕ 500 μ m), which differed for the inter-channel spacing, at 600, 700, or 900 μ m, respectively. Random-pore scaffolds, using the same technique, were taken as controls. Physical-mechanical characterization revealed high water uptake and favorable elastic mechanical behavior for all scaffolds, slightly reduced in the presence of cross-linking and enhanced with the 700 μ m-spaced micro-pattern. At MTT assay, mouse endothelial cell viability was >90% at day 1, 3 and 7, confirmed by visual examination with scanning electron microscopy (SEM). Intra-scaffold cell density, at fluorescence analysis, was higher for the 600 μ m-spaced and the 700 μ m-spaced micro-patterns over the others. The 700 μ m-spaced scaffold was selected for the in vivo testing, to be compared to the random-pore one. Neither type produced an inflammatory reaction; both showed excellent tissue ingrowth. Micro-patterned scaffolds enhanced neo-vascularization, demonstrated by immunofluorescent, semi-quantitative analyses. These findings support the use of micro-patterned porous scaffolds, with adequately spaced micro-channels, to promote neo-vascularization.